Pendulating or resonating? A case of echo-chambers in twitter. (2nd January 2022) - Gupta, Vedika; Dass, Pranav; Arora, Rameshwar
Abstract: Echo chambers, or circumstances in which one is only exposed to ideas that are similar to one's own, are becoming a growing problem for political debate in many democratic countries. We explore political echo chambers on Twitter. We investigate the conditions that lead to the creation of echo chambers in online social networks by proposing a basic model of information sharing in online social networks. Furthermore, we investigate the role of "opposition" party users in the development of echo chambers, who consume their information with a varied leaning but generate partisan content (with a single-sided leaning). Finally, we use our findings to forecast supporters and opponents on the basis of social and cultural characteristics.